Factor structure of Statistical Anxiety Scale (SAS) for a Malaysian sample - Abd Hamid, Harris Shah; Sulaiman, Muhamad Karimi (2014)
A negative relationship between statistics anxiety and performance in statistics course had been demonstrated among Malaysian students, but the factor structure of the anxiety measure had not been examined. This paper seeks to examine the factor structure of Statistical Anxiety Scale (SAS) in Malaysian samples. The scale was administered to 342 undergraduate students who took Introduction to Psychology course at a Malaysia university. Principal axis factor with Promax rotation revealed five factor solution and confirmatory factor analysis was performed in AMOS. The analysis produced a four factor model and an independent variable that fit the data. This divergence from the original three factor structure is worth exploring.